Synthesis of Thiazoline Complexes of Cu(ii), Ni(ii) and Co(ii) Transition Metals - Malik, Dinkar (Journal of Advance Research in Applied Science (ISSN 2208-2352), 2016)
The synthesis and characterization (elemental analysis, IR, electronic and magnetic susceptibility studies) of the transition metal complexes of Ni(II), Co(II) and Cu(II) with 2 - amino -4- (p- methoxy phenyl) thiazoline is described and complexes are obtained in 75-78% yield from the treatment of metal salts with ligand 2-amino- 4-(p-methoxy phenyl) thiazoline in 1:2 molar ratio in ethanolic medium. From the analytical and spectral data the stoichiometry of these complexes have been found to be of the type ML2X2 (where M = Cu (II), Co (II) and Ni (II)}.Evidences indicate that Ni(II), Cu(II) and Co(II) complexes exhibit octahedral and square planar geometry. The fungicidal activities of ligands and metal complexes were screened by growth method against various fungi i.e. Dreschlere setramera, Fusarium oxysporum, Macrophomera phaseoli at different concentrations. It is found that the activity decreases with decrease of concentration and the metal complexes are less toxic than the parent ligand.